478 Long-term Outcomes of Patients with Complications from Multi-modal Monitoring in Severe Traumatic Brain Injury. (1st March 2022) - Pease, Matthew; Nwachuku, Enyinna; Goldschmidt, Ezequiel; Jacobs, Rachel; Elmer, Jonathan; Okonkwo, David O.
Abstract : INTRODUCTION: Insertion of an external ventricular drain or intracranial pressure monitor is one of the most commonly performed neurosurgical procedures. Multi-modal invasive neuromonitoring (IN) is a mainstay of modern management of severe traumatic brain injury (TBI). Complication rates of IN placement are widely reported, but their effects on long-term outcomes following severe TBI are less studied. METHODS: We evaluated 599 patients with a severe TBI from November 2002 through December 2018 for IN-associated hemorrhage and infection. Trained neuropsychologists assessed outcomes at 3, 6, 12, and 24 months using the Glasgow Outcome Scale (GOS). We compared GOS between patients with and without IN-associated complications. RESULTS: IN-associated hemorrhage occurred in 62 patients out of 535 with post-placement CT scans (12%). Craniotomy was associated with increased risk for hemorrhage after monitor placement (53% vs 28%, p<0.001). Clinical outcomes did not differ in patients with IN-associated hemorrhage compared to those without. IN-associated infection occurred in 34 (7%) of 519 patients with post-IN placement cerebrospinal fluid cultures. Infection was associated with worse outcomes at 3 months (p=0.03), where the proportion of patients with favorable outcomes (p = 0.02) was decreased despite similar mortality (p = 0.24). Patients with an IN-related infection recovered by 6 months, at which point there were no differences in total GOS score or rates of favorable outcomes then or at later time points (p > 0.26). Patients with IN-associated infection trended towards improved outcomes over time with no patients with a GOS 3 or higher at 3 months falling below GOS 3 at a later point. IN-associated infection was associated with increased length of stay (p=0.01), but did not affect rates of shunting (p=0.99). CONCLUSION: Complications of IN in severe TBI are associated with delayed recovery but not long-term outcomes.